Qualitative analysis of emotional distress in burns, plastic and reconstructive surgery patients from the perspectives of cognitive and metacognitive models - Taylor-Bennett, Joseph; Capobianco, Lora; Wisely, Julie; Wells, Adrian (Frontiers in Psychiatry, 2024)
Burns and other injuries requiring plastic and/or reconstructive surgery (BPRS) are life changing, often unexpected, and increase the risk of psychiatric morbidity. There are no published studies we are aware of that explores the applicability of psychological models to BPRS patients. Cognitive behavioural therapy (CBT) is the benchmark treatment in mental health but may be less effective in physical health settings. Metacognitive therapy (MCT) can be more effective than CBT in mental health settings and shows promise in reducing anxiety and depression symptoms in people with cancer and cardiac disease. The present study explored the psychological experiences (feelings, thoughts, and coping strategies) of BPRS patients, and whether the concepts underpinning cognitive and metacognitive models can be elicited from these accounts. Semi-structured interviews were conducted with eleven patients recruited from a BPRS psychology service. Data was analysed using Thematic Analysis. Patients described a range of emotions including low mood, anxiety, anger, guilt, loss and negative thinking. From the perspective of the cognitive model, there were examples of each of ten pre-specified distorted thinking types (cognitive distortions) and patient talk seemed to fit problem-specific cognitive models. From the perspective of the metacognitive model all patients described the 'cognitive attentional syndrome' i.e. how they engaged in repetitive negative thinking (worry, rumination) and thought-focused regulation strategies. Patient talk also demonstrated both positive and negative metacognitive beliefs. The implications of applying the findings from each model to clinical practice are discussed. The metacognitive model may offer benefits in clinical practice that should be investigated further.